2010
DOI: 10.1080/00087114.2010.10589749
|View full text |Cite
|
Sign up to set email alerts
|

The Genotoxic and Antimitotic Properties of Helichrysum plicatum Herbal Teas Widely Consumed in Turkey

Abstract: -Helichrysum plicatum DC. subsp. plicatum (Asteraceae), (common name; everlasting) is a medicinal plant and natural product. For centuries, it has been used as tea in Turkey because of its medicinal properties. There are few reports in literature about genotoxic effects of this plant. The aim of this work is to evaluate the genotoxic and antimitotic effects on human lymphocyte cultures induced by aqueous (decoction) extracts of this plant which were assayed in different concentrations (0.01, 0.05, 0.1, 0.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[11] Recently, investigations on MN frequencies support the widely accepted assumption that MN is a product of early events in human carcinogenic processes. [12] Our results showed that all tested concentrations of A. calamus lowered the mutagenic effects of BLM by decreasing MN frequencies with the strongest activity obtained for highest concentration (40 µg/ml).…”
Section: Discussionmentioning
confidence: 64%
“…[11] Recently, investigations on MN frequencies support the widely accepted assumption that MN is a product of early events in human carcinogenic processes. [12] Our results showed that all tested concentrations of A. calamus lowered the mutagenic effects of BLM by decreasing MN frequencies with the strongest activity obtained for highest concentration (40 µg/ml).…”
Section: Discussionmentioning
confidence: 64%
“…For one of these, Helichrysum species, their capitulum heads or above-ground parts are known to be used in wound healing among the people. 10,11 H plicatum subsp. pseudoplicatum is the species of H plicatum plant recorded in the Erzurum region.…”
Section: Discussionmentioning
confidence: 99%
“…It is also mixed with honey against stomach ulcers and herbal ash mixed with cream or butter to treat facial wounds. [10][11][12] In wound healing treatment, antioxidant and antiseptic agents are used, and an increase in the number of fibroblast cells is desired. The release of oxygen radicals kills the invading foreign organisms, and the wound in the fibrin matrix is cleaned.…”
mentioning
confidence: 99%